2007
DOI: 10.2307/25549734
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Views of and Preferences for Sexual and Reproductive Health Services in Burkina Faso, Ghana, Malawi and Uganda

Abstract: Adolescents' views of and preferences for sexual and reproductive health services highlight promising directions and persistent challenges in preventing pregnancy and HIV and treating sexually-transmitted infections (STIs) in this population. Results from nationally-representative surveys of 12-19 yearolds in Burkina Faso, Ghana, Malawi and Uganda in 2004 show that contraceptive and STI services and HIV testing are still under-utilized. A substantial proportion of sexually-active adolescents do not know of any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
209
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(234 citation statements)
references
References 15 publications
18
209
2
5
Order By: Relevance
“…Other studies conducted across sub-Saharan Africa corroborate with the WHO study with respect to barriers to adolescent HTC (18,20,(22)(23)(24)(26)(27)(28)(29)(30)(31)(32). These studies identified major barriers as fear of a positive test, especially among those sexually active, and fear of stigma and discrimination, including being ostracized by friends and family.…”
Section: Willingness To Test and Barrierssupporting
confidence: 67%
See 1 more Smart Citation
“…Other studies conducted across sub-Saharan Africa corroborate with the WHO study with respect to barriers to adolescent HTC (18,20,(22)(23)(24)(26)(27)(28)(29)(30)(31)(32). These studies identified major barriers as fear of a positive test, especially among those sexually active, and fear of stigma and discrimination, including being ostracized by friends and family.…”
Section: Willingness To Test and Barrierssupporting
confidence: 67%
“…All three documents strongly recommend revision of age of consent policies to increase independent access to HTC for adolescents. (17)(18)(19)(20), East (18,(21)(22)(23), and southern Africa (24)(25)(26). The proportion of adolescents willing to test differed within and between some countries with respect to factors including gender, geographical residence, socio-cultural norms, and HIV knowledge and risk perception of participants.…”
Section: Hiv Testing For African Adolescentsmentioning
confidence: 99%
“…12 Approximately a third of adolescents aged 15-19 years reported having a close friend who tried to end a pregnancy, as did a fifth of those aged 12-14. 5 Inadequate knowledge of sexual and reproductive health, 15 reluctance to access health services, 16 early marriage and sexual debut, 17 and low rates of contraceptive use make Malawian teens particularly vulnerable to sexual and reproductive health problems, including complications of unsafe abortion.…”
Section: Unintended Pregnancy and Unsafe Abortion In Malawimentioning
confidence: 99%
“…In Malawi, the Yao and the Lomwe typically practise initiation ceremonies for adolescent boys that include circumcision, as well as rituals involving receiving instruction for future life as a man (Stannus and Davey 1913 (Munthali and Zulu 2007). It should be noted that approximately 80 per cent of youth in Malawi have had sex before the age of 18 years, suggesting that, in terms of using circumcision as an HIV-prevention strategy, earlier ages of circumcision might be more optimal (Biddlecom et al 2007). …”
Section: Cultural Practices and Prevalencementioning
confidence: 99%